2019
DOI: 10.19027/jai.18.2.182-192
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive and cannibalistic behavior of African catfish larvae: effect of different doses of methyltestosteron injecting to female broodstock and larval stocking densities

Abstract: This study aimed to evaluate the effect of 17α-methyltestosterone hormone (MT) injecting to female broodstocks and stocking densities on the aggressive and cannibalistic behavior of African catfish larvae. Two-day-old post-hatching larvae were used in this experiment. Larval rearing was started at three-day-old post-hatching (body weight 0.004 ± 0.003 g and total length 0.2 ± 0.05 cm) in a 40 cm×30 cm× 25 cm rearing aquaria. This study used a completed randomized factorial design which consisted of two factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…However, in general, several studies have reported that exogenous administration of estradiol-17 causes a significant decrease in testosterone concentration accompanied by an increase in estradiol concentration in fish (Yuan et al, 2012;Khara et al, 2013). Another impact of increased testosterone was an increase in aggressiveness in fish which was closely related to the incidence of cannibalism in fish (Maruska and Fernald, 2010;Black et al, 2011;Kania et al, 2012;Chang et al, 2012;Peterson et al, 2013;Alcazar et al, 2016;Rahmadiah et al, 2019). Alcazar et al (2016) stated that there was a relationship between steroid hormones and aggression in fish.…”
Section: Discussionmentioning
confidence: 99%
“…However, in general, several studies have reported that exogenous administration of estradiol-17 causes a significant decrease in testosterone concentration accompanied by an increase in estradiol concentration in fish (Yuan et al, 2012;Khara et al, 2013). Another impact of increased testosterone was an increase in aggressiveness in fish which was closely related to the incidence of cannibalism in fish (Maruska and Fernald, 2010;Black et al, 2011;Kania et al, 2012;Chang et al, 2012;Peterson et al, 2013;Alcazar et al, 2016;Rahmadiah et al, 2019). Alcazar et al (2016) stated that there was a relationship between steroid hormones and aggression in fish.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have been reported that overcrowding in aquaculture system could result in lower survival and growth and increase stress (Manley et al, 2014;Qun et al, 2016). In African catfish culture, mortality might also be caused by cannibalistic behaviour in particular when the fish was varied in size (Biu et al, 2015;Rahmadiah et al, 2019). The fish growth in biofloc systems generally showed higher performance than that of the control, regardless the fish density.…”
Section: Discussionmentioning
confidence: 99%
“…The high androgen hormone level during the parent's gonad maturation will be inherited by the catfish larvae which then becomes a trigger for aggressive behaviour in larvae (Zairin et al, 1992). Rahmadiah et al (2019) worked with three methyl testosterone (MT) concentrations and two stocking densities. The results showed that the larvae from female broodstocks injected with MT 2 μg/g body weight and stocking densities 6000/m 2 increased the aggressiveness of swim, but decreased cannibalism.…”
Section: Introductionmentioning
confidence: 99%